Diagnostic approach to tinea capitis with kerion: A retrospective study. Issue 5 (5th May 2022) - Shemer, Avner; Lyakhovitsky, Anna; Kaplan, Baruch; Kassem, Riad; Daniel, Ralph; Caspi, Tomm; Galili, Eran
Abstract: Background: Kerion is an inflammatory type of tinea capitis manifesting as boggy crusted nodules. Diagnosis of kerion is often challenging due to high rates of false‐negative mycological samples. Methods: A retrospective study among children with kerion, prior to antifungal treatment, was conducted to assess rates of false‐negative mycological samples. Specimens for direct microscopy and fungal culture were collected at baseline and after administration of an oral antibiotic course, with or without an oral steroid course. Kerion was categorized as highly inflammatory when a painful, moist scalp nodule with spontaneous purulent discharge or exuberant crust was present, or mildly inflammatory when an erythematous, dry scalp nodule was seen. Results: Twenty‐three children (mean age 7.9 ± 3.0 years) were included in the study. Trichophyton tonsurans was the most common species isolated (69.6%). Highly inflammatory kerions were significantly more likely to be culture negative before treatment than mildly inflammatory kerions (80% vs. 16.7%, p  < .01). Non‐inflammatory tinea capitis lesions ( n  = 13) were culture positive in all cases. Following a combined oral antibiotic and steroid course given to most highly inflammatory kerions ( n  = 11/13), higher rates of positive fungal cultures were found compared to baseline (90.9% vs. 18.2%, p  < .01). Conclusion: High rates of negative fungal cultures were found only in highly inflammatory kerion. Sampling a highly inflammatory kerion after a combined oral antibiotic and steroid course improved rates of positive fungal cultures. In addition, sampling of non‐inflammatory tinea capitis lesions (when present in addition to the kerion) had the highest culture sensitivity.